Technology in older hands: A pilot study on digital literacy and attitudinal changes in old age Technology in older hands - Ureta Fernández, María del Pilar; Agüero Jiménez, Amaru; Cerda Díez, María Fernanda (Revista Española de Comunicación en Salud, 2026)
Introduction: The rapid digital transformation of contemporary societies poses new challenges for older adults, who generally present lower levels of digital literacy compared to other age groups. Objective: This pilot study aimed to evaluate the impact of a structured digital literacy intervention on attitudes toward and use of smartphones among older adults in Chile. Methodology: A quasi-experimental pretest–posttest design was applied to 71 participants (≥60 years) who completed a four-session program focused on smartphone use for communication, information searching, and online procedures. Results: Quantitative analysis showed significant improvements across all evaluated dimensions: perceived usefulness, comfort, control, and frequency of use (Wilcoxon test, p<0.05). Effect sizes ranged from small to moderate, with comfort of use showing the greatest change. Multivariate analysis revealed that age, gender, and living arrangements influenced post-intervention results, highlighting the need for differentiated approaches. Conclusion: Beyond technical skills, the intervention fostered positive attitudinal changes, promoting autonomy. These findings suggest that small, personalized, and participatory programs can effectively reduce the grey digital divide, contributing to the technological inclusion of older adults.